Penerapan Media Domino Berbasis Gambar untuk Meningkatkan Kosakata Bahasa Arab Siswa Kelas IV: Studi Eksperimen pada Siswa Kelas IV - Jefriadi, Zahrah Anastia Sadri; Syamsuddin, Naidin; Mustafa, Mustafa (Pedagogical Education and Review of Linguistics, 2025)
This thesis discusses the application of image-based domino media to improve Arabic vocabulary. This study aims (1) to find out how image-based domino media can improve Arabic vocabulary of fourth grade students of SDIT Al-Bashirah Palopo, (2) to find out whether image-based domino media can improve Arabic vocabulary of fourth grade students of SDIT Al-Bashirah Palopo. This type of research is classroom action research, the data collection methods are action observation, field notes, and test sheets. The results of this study are (1) classroom action research conducted by researchers can be concluded that the mastery and results of improving Arabic vocabulary of fourth grade students of SDIT Al-Bashirah Palopo can be increased through the application of Image-Based Domino media (2) The increase in percentage in cycle I can be seen that out of 21 students, 11 students have completed the learning with a percentage of (52.3%), while 10 students have not completed it with a percentage of (47.6%). As for cycle II, all 21 students have completed the learning with a percentage of (100%). From cycle I to cycle II there was an increase in learning outcomes of (47.7%). Thus, in cycle II the learning outcomes are said to be complete.